(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
In recent years, armed groups and individual militants of jihadist inspiration have planned and, in some cases, actually carried out terrorist attacks in the West using various types of firearms – some of them with severe consequences. After presenting an overview of the literature available on the subject, this contribution focuses on the topic of the process of weapon selection at the organizational level and addresses the issue of the use and acquisition of firearms in jihadist attacks in the West, also on the basis of original data. Keywords: terrorism, firearms, weapon selection, jihadism, crime